2002
DOI: 10.1073/pnas.062447999
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer action in trans is permitted throughout the Drosophila genome

Abstract: Interactions between paired homologous genes can lead to changes in gene expression. Such trans-regulatory effects exemplify transvection and are displayed by many genes in Drosophila, in which homologous chromosomes are paired somatically. Transvection involving the yellow cuticle pigmentation gene can occur by at least two mechanisms, one involving the trans-action of enhancers on a paired promoter and a second involving pairingmediated bypass of a chromatin insulator. A system was developed to evaluate whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
54
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 55 publications
3
54
0
1
Order By: Relevance
“…Our approach was informed by a prior experiment that used transposons carrying yellow alleles, including flanking regulatory sequences, that were designed to mimic mutations known to support enhancer action in trans at the natural yellow locus. That study showed the Drosophila genome to be generally permissive to transvection, demonstrating the feasibility of a transgenic approach to the analysis of enhancer action in trans (Chen et al 2002). In the present study, our goal was to construct transgenes based on fluorescent reporters such as GFP and mCherry to facilitate quantification of gene expression and to provide cellular resolution of transgene activation.…”
mentioning
confidence: 99%
“…Our approach was informed by a prior experiment that used transposons carrying yellow alleles, including flanking regulatory sequences, that were designed to mimic mutations known to support enhancer action in trans at the natural yellow locus. That study showed the Drosophila genome to be generally permissive to transvection, demonstrating the feasibility of a transgenic approach to the analysis of enhancer action in trans (Chen et al 2002). In the present study, our goal was to construct transgenes based on fluorescent reporters such as GFP and mCherry to facilitate quantification of gene expression and to provide cellular resolution of transgene activation.…”
mentioning
confidence: 99%
“…Since this special set of mutations is required to detect transvection, it is unknown exactly how prevalent transvection is in Drosophila. However, on the basis of known pairing frequencies of homologous loci (Golic and Golic 1996b;Vazquez et al 2002;Lowenstein et al 2004;Harmon and Sedat 2005) and the work of Chen et al (2002), in which it was shown using a Cre and FLPmediated transgene coplacement system that the Drosophila genome is generally permissive for transvection, it is likely that the dozen or so known instances of transvection represent only a small fraction of all transregulatory effects in Drosophila.…”
mentioning
confidence: 99%
“…Evidence for enhancer action in trans has been uncovered at a handful of genes in the Drosophila genome, often providing an explanation for unexpected intragenic complementation of loss-of-function alleles (Lewis 1954;Gelbart 1982;Geyer et al 1990;Leiserson et al 1994;Hendrickson and Sakonju 1995;Casares et al 1997;Morris et al 1998;Southworth and Kennison 2002;Marin et al 2004;Coulthard et al 2005;Gohl et al 2008;Juni and Yamamoto 2009) paired mutant and wild-type alleles (Gibson et al 2000;Lum and Merritt 2011;Bing et al 2014). More recently, transgenic approaches based on site-specific recombination have been developed for Drosophila to query specific enhancer fragments and genomic positions for support of transvection (Chen et al 2002;Kravchenko et al 2005;Bateman et al 2012a;Mellert and Truman 2012; also see Kassis et al 1991). Thus far, transvection has been observed at all genomic insertion sites tested, suggesting that the Drosophila genome is generally permissive to enhancer action in trans.…”
mentioning
confidence: 99%
“…More recently, transgenic approaches based on site-specific recombination have been developed for Drosophila to query specific enhancer fragments and genomic positions for support of transvection (Chen et al 2002;Kravchenko et al 2005;Bateman et al 2012a;Mellert and Truman 2012; also see Kassis et al 1991). Thus far, transvection has been observed at all genomic insertion sites tested, suggesting that the Drosophila genome is generally permissive to enhancer action in trans.…”
mentioning
confidence: 99%